Evolution of structural and electrophysical parameters of Ni/SiC contacts at rapid thermal annealing - Litvinov, V.L.; Demakov, K.D.; Agueev, O.A.; Svetlichny, A.M.; Konakova, R.V.; Lytvyn, P.M.; Lytvyn, O.S.; Milenin, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
Using X-ray phase analysis, Auger electron spectroscopy and atomic force microscopy, we investigated structural-phase transformations in the Ni/n-21R-SiC system induced by rapid thermal annealing in a vacuum (pressure of 10-² Pa) in the 450-1100 °С temperature range. It was found that modification of contact I-V curves from barrier-type to ohmic is due to appearance of local contact areas with different barrier heights (among them areas with ohmic conduction). Generation of the above nonuniformities results from intense heterodiffusion of the system components, as well as formation and recrystallization of various nickel silicide phases (differing in stoichiometry) and degradation of planar uniformity of both interface and Ni film.